Analisis Penerapan Sistem Pencatatan Akuntasi berbasis SAK EMKM terhadap Laporan Keuangan pada CV Kreasi Sejahtera Abadi Desa Firdaus Kabupaten Serdang Bedagai - Khairul Faiz Batubara; Nurlaila Nurlaila; Nurul Inayah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study is to determine the Application of the EMKM SAK Based Accounting Recording System to Financial Statements on CV. Kreasi Sejahtera Abadi of Firdaus Village, Serdang Bedagai Regency. This research uses qualitative research methods with a qualitative descriptive approach and the data collection techniques used are interviews with business owners and the acquisition of data and information in the form of financial statement documents. The results of this study show that CV. Kreasi Sejahtera Abadi has implemented its company's accounting recording system but has not been structured according to SAK EMKM standards, namely the existence of income statements, balance sheets and notes to financial statements, where CV. Kreasi Sejahtera Abadi has made financial statements in the form of income statements, statements of financial position (balance sheet) both of which are still simple and do not make and apply financial statements in the form of notes to financial statements.